2021
DOI: 10.3390/ijerph18137183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bioaerosol Inactivation Ability of Chitosan-Coated Antimicrobial Filters

Abstract: This work considers the enhancement of indoor bioaerosol removal efficiency by liquid coating of the antimicrobial agent chitosan onto polypropylene fibrous filters (CCFs). Escherichia coli (E. coli) and Bacillus subtilis (B. subtilis) were chosen as the tested bioaerosols. The results revealed that 2.5% (w/w) of CCFs have significantly higher bioaerosol survival capability (23% and 34% of E. coli and B. subtilis, respectively), compared to an untreated filter (65% and 64% for E. coli and B. subtilis, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“… Ref Results Microorganism or pollutant Materials [ 63 ] (Particulate matter 2.5 > 98.0%, particulate matter10 > 98.4%), high flow rate (1.9 m s −-1 after 1 h) a low (21 Pa) pressure drop. Particulate matter Chitosan/ poly(methylmethacrylate)/polydimethylsiloxane [ 64 ] 99.3% filtration efficacy for NaCl, and 99.4% for DEHS aerosol (Diisooctyl sebacate) Diisooctyl sebacate aerosol N-halamine/ poly(vinyl alcohol)/ chitosan [ 65 ] In 3 h of operating, 80.1% bioaerosol was removed B. subtilis and E. coli Chitosan/ polypropylene [ 66 ] After 120 min, the survival rate of microorganisms on pristine nylon, nylon/chitosan, as well as chitosan dipped nylon-6 nano-fibrous filters decreased to 8.4%, 7.1%, and 2.8%. E. coli and B. subtilis Nylon/chitosan [ 68 ] 99.69% efficiency for particulate matter 2.5 and 99.89% removal efficiency for particulate matter 10 Particulate matters Cholinium alginate [ 69 ] 94.92 and 96.94% inactivation Bacteriophage phi 6 and SARS-CoV-2 Delta variant Calcium alginate films [ 70 ] 99.99% effectiveness toward coronavirus, with low cytotoxicity Coronavirus Alginate/copper sulfate [ 71 ] 95% efficiency to capture aerosols Aerosols Gelatin/β–cyclodextrin [ 72 ] Capture effectiveness of modified HEPA filter was up to 2730 pfu/mm 2 within 10 min.…”
Section: The Role Of Biopolymers and Other Natural Materials In The F...mentioning
confidence: 99%
See 1 more Smart Citation
“… Ref Results Microorganism or pollutant Materials [ 63 ] (Particulate matter 2.5 > 98.0%, particulate matter10 > 98.4%), high flow rate (1.9 m s −-1 after 1 h) a low (21 Pa) pressure drop. Particulate matter Chitosan/ poly(methylmethacrylate)/polydimethylsiloxane [ 64 ] 99.3% filtration efficacy for NaCl, and 99.4% for DEHS aerosol (Diisooctyl sebacate) Diisooctyl sebacate aerosol N-halamine/ poly(vinyl alcohol)/ chitosan [ 65 ] In 3 h of operating, 80.1% bioaerosol was removed B. subtilis and E. coli Chitosan/ polypropylene [ 66 ] After 120 min, the survival rate of microorganisms on pristine nylon, nylon/chitosan, as well as chitosan dipped nylon-6 nano-fibrous filters decreased to 8.4%, 7.1%, and 2.8%. E. coli and B. subtilis Nylon/chitosan [ 68 ] 99.69% efficiency for particulate matter 2.5 and 99.89% removal efficiency for particulate matter 10 Particulate matters Cholinium alginate [ 69 ] 94.92 and 96.94% inactivation Bacteriophage phi 6 and SARS-CoV-2 Delta variant Calcium alginate films [ 70 ] 99.99% effectiveness toward coronavirus, with low cytotoxicity Coronavirus Alginate/copper sulfate [ 71 ] 95% efficiency to capture aerosols Aerosols Gelatin/β–cyclodextrin [ 72 ] Capture effectiveness of modified HEPA filter was up to 2730 pfu/mm 2 within 10 min.…”
Section: The Role Of Biopolymers and Other Natural Materials In The F...mentioning
confidence: 99%
“…Hsu et al evaluated the inactivation ability of bioaerosols by chitosan-coated antimicrobial filters [ 65 ]. In this study, chitosan as an antimicrobial agent has coated on polypropylene fibrous filters through the liquid coating process, and the development of removal efficacy of indoor bioaerosols (tested bioaerosols: B. subtilis and E. coli ) was considered.…”
Section: The Role Of Biopolymers and Other Natural Materials In The F...mentioning
confidence: 99%
“…The simultaneous removal and inactivation technologies for bioaerosols in ventilation systems need further study. Some researchers tried to solve the problem by coating or growing antimicrobial components onto filter fibers. , Xiao et al incorporated silver nanoparticles into poly­(vinylidene difluoride) nanofiber membranes. The study demonstrated that the modified membranes could resist Staphylococcus aureus and Escherichia coli with a bacterial reduction rate of 99.6% and capture efficiency of 99.95% with a pressure drop of 137.5 Pa at 85 L/min .…”
Section: Introductionmentioning
confidence: 99%
“…However, this liquiddisinfectant intervening technique is not suitable for peroneal-occupied space because of a potential visual-annoying problem. Hsu et al [16] used the chitosan-coated antimicrobial filter to inactivate E. coli and Bacillus subtilis bioaerosols in the environmental-controlled chamber. The results revealed that 2.5% (w/w) of chitosan-coated antimicrobial filters have significantly more additional bioaerosol inactivating ability than conventional non-chemical coated air filters.…”
Section: Introductionmentioning
confidence: 99%